Influence of Larval Habitat Environmental Characteristics on Culicidae Immature Abundance and Body Size of Adult Aedes aegypti - David, Mariana Rocha; Dantas, Edson Santos; Maciel-de-Freitas, Rafael; Codeço, Cláudia Torres; Prast, Alex Enrich; Lourenço-de-Oliveira, Ricardo (Frontiers in Ecology and Evolution, 2021)
Aedes aegypti is adapted to live in close association with human dwellings, where it lays eggs in several man-made container types with a broad range of size, shape and material. Biotic and abiotic conditions of larval habitats determine the abundance and body size of emerging adult mosquitoes. Here, we estimated the predictive potential of physicochemical water variables for Culicidae immature abundance and Ae. aegypti adult body size in four neighborhoods with distinct urban landscapes in Rio de Janeiro, Brazil. Domestic water holding containers (N=240) were inspected for the presence of Culicidae immatures and had several physiochemical parameters measured. Larvae and pupae were counted, and pupae were reared to the adult stage for taxonomic identification. Dry weight and wing size were measured for Ae. aegypti adult mosquitoes (N=981). The association between larval habitat parameters with Culicidae abundance and Ae. aegypti body size data was estimated through linear mixed models and generalized linear mixed models, respectively, with the neighborhood as random effect. The abundance of immature Culicidae in larval habitats (from which >90% of adults emerging from field collected pupae were Ae. aegypti) was positively associated with container volume and the dissolved organic carbon concentration (DOC). Female average dry weight and male and female wing lengths were positively associated with larval habitat temperature whereas male average dry weight was positively related to water conductivity. Aedes aegypti originating from larval habitats with Ae. albopictus exhibited no differences in median wing length and dry body weight when compared with specimens collected in containers exclusively colonized by Ae. aegypti. These results demonstrate that container water volume (characteristic easily observed in the field) and DOC (often higher in unmanaged water holding recipients) is related to higher Ae. aegypti immature density. Estimating the effects of physicochemical water variables on immature abundance and adult body size can provide valuable information for predicting arbovirus transmission risk in endemic settings.